Generalized Ellipsometry Measurements of Crystalline Thin Film and Bulk Tin Oxide - Jellison, Gerald E.; Hermann, Raphaël P.; Specht, Elliot D.; Boatner, Lynn A.; Zac Ward, T.; Herklotz, Andreas (Physica status solidi. A, Applications and materials science, 2022)
Several bulk and thin‐film crystals of SnO2 are grown and examined using generalized ellipsometry techniques. The bulk samples are grown using the chemical vapor transport technique and thin films of SnO2 are grown using the pulsed laser deposition technique. The bulk samples are examined using the two‐modulator generalized ellipsometry microscope (2‐MGEM) at normal incidence and the spectroscopic two‐modulator generalized ellipsometer (2‐MGE). The spectroscopic optical functions of tin oxide are then obtained using the 2‐MGE from 1.46 to 6.2 eV. The material is highly birefringent, and the ordinary bandgap is less than the extraordinary band edge. 2‐MGE measurements are also made on thin‐film samples of crystalline tin oxide grown on sapphire and rutile, showing no cross polarization. Because of the complicated morphology of the tin oxide films grown on sapphire, the ellipsometry data are simulated using the Tauc–Lorentz model. Films grown on rutile had the optic axis perpendicular to the sample surface, but the film is strained, resulting in a more complicated ellipsometric spectrum. These films are modeled using the air/surface roughness/tin oxide/interface/rutile model, where the roughness and interface are modeled using the incomplete Beta function. Generalized ellipsometry measurements are used to determine the ordinary (o) and extraordinary (e) refractive index and absorption coefficients of uniaxial tin oxide (SnO2). As shown in the figure, the birefringence is large and ordinary optical absorption occurs at a lower energy then extraordinary optical absorption. These measurements are used to model the optical functions of crystalline tin oxide films.